2022
DOI: 10.3390/agriculture12020311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shallow Groundwater Depth and Nitrogen Application Level on Soil Water and Nitrate Content, Growth and Yield of Winter Wheat

Abstract: The large amount of nitrogen application on the North China Plain has caused a serious negative impact on the sustainable development of regional agriculture and ecological environmental protection. Our aim was to explore the effects of nitrogen fertilization rate and groundwater depth on growth attributes, soil-water and soil-fertilizer contents, and the winter wheat yield. Experiments were carried out in micro-lysimeters at groundwater depths of 60, 90, 120, and 150 cm on the basis of 0, 150, 240, and 300 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…WTD may be deeper, and the upper soil moisture was too late to be replenished with limited irrigation ( Supplementary Figures S2C, D ). High N application rate (>150–240 kg/ha) significantly enlarged soil inorganic nitrogen content and deepened soil drought ( Wang et al., 2016b ; Zhang et al., 2020 ; She et al., 2022 ). Less water and more nitrogen in soil resulted in the imbalance of water and fertilizer supply for the crop, water stress limited the nitrogen availability ( Gu et al., 2015 ), and a high N application rate inhibited crop growth and crop water absorption ( Figures 2B–D , 3B–D , Supplementary Figures S2C, D ) ( Rasmussen et al., 2015 ; Liu et al., 2018 ), resulting in yield reduction ( Figures 6 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WTD may be deeper, and the upper soil moisture was too late to be replenished with limited irrigation ( Supplementary Figures S2C, D ). High N application rate (>150–240 kg/ha) significantly enlarged soil inorganic nitrogen content and deepened soil drought ( Wang et al., 2016b ; Zhang et al., 2020 ; She et al., 2022 ). Less water and more nitrogen in soil resulted in the imbalance of water and fertilizer supply for the crop, water stress limited the nitrogen availability ( Gu et al., 2015 ), and a high N application rate inhibited crop growth and crop water absorption ( Figures 2B–D , 3B–D , Supplementary Figures S2C, D ) ( Rasmussen et al., 2015 ; Liu et al., 2018 ), resulting in yield reduction ( Figures 6 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of the lysimeter was 40 cm, the height was 1.0-1.9 m, the side had soil extraction holes, and the inside was equipped with soil moisture monitoring probes and soil solution extractors. The details of the lysimeter were described by She et al (2022). The water level scale on the Mariotte bottle was used to record the groundwater consumption.…”
Section: Experimental Sitementioning
confidence: 99%
“…Meanwhile, soil moisture status and crop growth interact and constrain each other [1,2]. Soil moisture status causes diverse responses in crops that affect everything from morphology to physiology, so the presence of shallow groundwater will inevitably have an impact on the process of crop growth and evapotranspiration (ET) [3]. In recent years, many scholars have conducted extensive research on the impact of shallow groundwater on crops.…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al [7] found that the effect of a groundwater depth of 2 m on crop growth was greater than that of a groundwater depth of 3 and 4 m, which showed that the larger the groundwater depth, the more unfavorable to the plant height, leaf area index (LAI) and dry matter accumulation (DMA) of winter wheat. She et al [8] concluded that compared to groundwater depths of 3 and 4 m, the groundwater depth of 2 m helped to extend the rapid growth time and increase the LAI of maize. Wang [9] controlled the groundwater depth at 1, 2, 3 and 4 m and found that shallow groundwater helped to accelerate the reproductive process of plants and increase the LAI, which in turn enhanced plant photosynthesis and ET.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the N use e ciency of crops is calculated using the difference value method (Yang, et al, 2021;She, et al, 2022). However, this method cannot distinguish whether the N absorbed by crops comes from the soil or fertilizer.…”
Section: Introductionmentioning
confidence: 99%